Alteridades possíveis com jovens estrangeiros : diferenças e diversidade cultural em documentários - Nascimento, Livia de Almeida (2022)
This study investigates how documentary films dealing with cultural differences and diversity contribute to experiences of alterity in the adaptation process of young immigrants and refugees, especially in poetics that include other artistic languages. It also discusses how intercultural relations between local people and foreigners take place in integration and inclusion processes within educational contexts. To this end, we conduct a comparative analysis between the films Bagages (Canada, 2017) and Cara do Mundo (Brazil, 2016), based on studies by Mikhail Bakhtin (2003) that address alterity; on experiences by Alain Bergala (2008) about the potential of cinema in education and with young adults, as well as on ideas by Denys Cuche (1999) and Homi K. Bhabha (1998) involving cultural differences and diversity. Using criteria that respect categories such as the context in which the films were made, we analyze how the documentary narratives studied were appropriated in specific social processes and discuss the use of these audiovisual products in the process of building experiences of alterity and social insertion involving young immigrants and refugees.